Effect of pyrogallol compounds dosage on mechanical properties of epoxy coating - Huang Weitao; Yao Yong; Deng Jiayi; Liu Yuqi; Guo Minlong; Huang Congshu; Liang Yu; Mo Yeqiang (e-Polymers)
Anticorrosive coatings are considered to be one of the most economical and effective means of protection. The adhesion of the coating is defined as the strength of the interfacial bond between the coating and the substrate, which directly determines the protective life of the coating. In this work, the epoxy–(5-{5-[2-(3,4,5-trihydroxyphenyl)-1H-1,3-benzodiazol-6-yl]-1H-1,3-benzodiazol-2-yl}benz-1,2,3-triol} (EP-BIB) composite coating was obtained by adding different mass fractions of BIB to the EP coating. The effect of mass fraction of BIB on the mechanical properties of composite coating were studied by Elongation at break, tensile shear strength, as well as Peel strength. The results showed that the mechanical properties of composite coating could be improved by adding an appropriate amount of BIB. The elongation at break, tensile shear strength, and peel strength of composite coating became better initially and then worse with the increase in BIB content in the composite coating. The composite coating with 0.9% (mass fraction) BIB had the elongation at break of 10.37 ± 0.53%, an optimal shear strength of 12.51 ± 0.48 MPa, and a maximum peel strength of 4.78 ± 0.54 N·mm−1.